Analisis Kepuasan Wisatawan Berdasarkan Unsur Destinasi Wisata Di Pulau Pramuka, Kepulauan Seribu, Jakarta - Fitriana, Rina; Fakhira, Rahmah (Jurnal Ilmiah Pariwisata, 2019)
This study aims to determine tourists satisfaction based on destination elements (attractions, facilities, infrastructure, transportation, and hospitality) in Pulau Pramuka, KepulauanSeribu, DKI Jakarta. The research method used is this study is descriptive quantitative method with purposive sampling technique. The sample of this study consists of 100 tourists who had visited Pramuka Island with an error margin of 10%. It is revealed that the average value of tourist satisfaction based on the five elements of tourist destinations is 3.91. If the value combined with tables of visitor perception intervals, it can be concluded that tourist satisfaction based on elements of tourist destinations in PulauPramuka is classified as SATISFIED. It proves that actually that the elements of tourist destinations in PulauPramuka have been well enough in attracting the tourists to visit or to make a tour.